2005
DOI: 10.1063/1.2132072
|View full text |Cite
|
Sign up to set email alerts
|

Hole-injecting conducting-polymer compositions for highly efficient and stable organic light-emitting diodes

Abstract: This letter introduces conducting polymer compositions which can be used for hole-injection layer in organic light-emitting diodes. The compositions are composed of poly (3,4-ethylenedioxythiophene) (PEDOT), polystyrene sulfonic acid (PSS) and a perfluorinated ionomer. The films based on these compositions showed much higher workfunction (∼5.3–5.7eV) than conventional PEDOT/PSS (∼5.0–5.2eV). When we fabricated blue polymer light-emitting diodes by using these compositions as a hole-injection layer, the lumines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 10 publications
2
51
0
1
Order By: Relevance
“…[ 6 ] The anionic polyelectrolyte Nafi on, which is also an acid, is found to give the opposite effect compared to cationic polyelectrolytes. A thin fi lm of Nafi on on ITO is found to increase the work function by 0.5 eV, [21][22][23] which indicates that Nafi on can modify the metal work function. Another anionic polyelectrolyte is poly(4-styrenesulfonic acid) (H-PSS), a component of PEDOT:PSS formulations.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] The anionic polyelectrolyte Nafi on, which is also an acid, is found to give the opposite effect compared to cationic polyelectrolytes. A thin fi lm of Nafi on on ITO is found to increase the work function by 0.5 eV, [21][22][23] which indicates that Nafi on can modify the metal work function. Another anionic polyelectrolyte is poly(4-styrenesulfonic acid) (H-PSS), a component of PEDOT:PSS formulations.…”
Section: Introductionmentioning
confidence: 99%
“…24 Lee et al showed that adding PFI to the HTL reduced the operating voltage and increased the device luminescent efficiency. 21 Adding PFI to the HTL has also been shown to increase device lifetime. 25 Similar positive results have also been achieved by spin coating a thin, interfacial layer of PFI on top of the HTL, 23 but it is much easier from a processing standpoint to blend PFI with S-P3MEET and reduce the number of fabrication steps.…”
Section: -12mentioning
confidence: 99%
“…PFI has been shown to be successful at creating high F HTLs for blue organic light emitting diodes (OLEDs). [21][22][23] Like low band-gap polymers, blue emitting polymers oen have a large IP. As an example, for poly(9,9-dioctyluorene) IP ¼ 5.9 eV.…”
Section: -12mentioning
confidence: 99%
“…Electronic grade PEDOT:PSS can be reformulated by addition of a 5 wt % Nafion ® perfluorinated resin solution in a water/alcohol mixture ͑Aldrich͒ to obtain a work function of 5.7 eV. 10 Addition of a Nafion solution to pH-modified PEDOT:PSS dispersions is considered less feasible, since it introduces an additional acidic component to the formulation. It is, however, possible to apply a thin Nafion-only layer that raises the work function of the underlying anode.…”
Section: High Work Function Transparent Middle Electrode For Organic mentioning
confidence: 99%